Conformationally Flexible Bis(9‐fluorenylidene)porphyrin Diradicaloids - Zhang, Hejian; Phan, Hoa; Herng, Tun Seng; Gopalakrishna, Tullimilli Y.; Zeng, Wangdong; Ding, Jun; Wu, Jishan (Angewandte Chemie International Edition, 2017)
A stable 5,10‐bis(9‐fluorenylidene)porphyrin (Por‐Fl) diradicaloid was synthesized. It shows a quinoidal, saddle‐shaped geometry in the single crystal but can be thermally populated to a triplet diradical both in solution and in the solid state. Coordination with the Ni2+ ion (Por‐Fl‐Ni) does not significantly change the contorted conformation but reduces the singlet–triplet gap. Heat‐induced geometric change can explain the observed paramagnetic properties as well as unusual hysteresis in SQUID measurements. On the other hand, protonation (Por‐Fl‐2H+) dramatically changes the conformation while maintains the closed‐shell electronic structure. Our studies demonstrate how heat, coordination, and protonation affect the geometry, diradical character, and physical properties of conformationally flexible open‐shell singlet diradicaloids. Protonation with a twist! A quinoidal bis(9‐fluorenylidene)porphyrin and its NiII complex showed closed‐shell saddle‐shaped geometry in the crystalline state but they can be thermally populated to paramagnetic triplet species through geometric change. Protonation also dramatically changes the conformation and physical properties.